Three-dimensional cell-culture platform based on hydrogel with tunable microenvironmental properties to improve insulin-secreting function of MIN6 cells. (March 2021) - Zhang, Miao; Yan, Sen; Xu, Xueqin; Yu, Tingting; Guo, Zhaobin; Ma, Ming; Zhang, Yi; Gu, Zhuxiao; Feng, Yiwei; Du, Chunyue; Wan, Mengqi; Hu, Ke; et al.
Abstract: Pancreatic β-cells have been reported to be mechanosensitive to cellular microenvironments, and subjecting the cells to more physiologically relevant microenvironments can produce better results than when subjecting them to the conventional two-dimensional (2D) cell-culture conditions. In this work, we propose a novel three-dimensional (3D) strategy for inducing multicellular spheroid formation based on hydrogels with tunable mechanical and interfacial properties. The results indicate that MIN6 cells can sense the substrates and form tightly clustered monolayers or multicellular spheroids on hydrogels with tunable physical properties. Compared to the conventional 2D cell-culture system, the glucose sensitivities of the MIN6 cells cultured in the 3D culture model is enhanced greatly and their insulin content (relative to the amount of protein) is increased 7.3–7.9 folds. Moreover, the relative gene and protein expression levels of some key factors such as Pdx1, NeuroD1, Piezo1, and Rac1 in the MIN6 cells are significantly higher on the 3D platform, compared to the 2D control group. We believe that this 3D cell-culture system developed for the generation of multicellular spheroids will be a promising platform for diabetes treatment in clinical islet transplantation.